Pengaruh Ketersediaan Barang dan Kualitas Layanan terhadap Ulasan Pembeli pada Platform E-Commerce Tokoteknopro - Tomy Rohmat Ardiyanto; Ana Ramadhayanti (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The purpose of this study is to examine how service quality and product availability impact customer reviews on the TokoteknoPro e-commerce platform. Customer reviews play a crucial role in shaping consumer purchasing decisions in today's market. Customer perceptions and satisfaction are significantly influenced by two key factors: service quality and product availability. This research employed quantitative methods, using a survey distributed to one hundred active TokoteknoPro users to gather data. The collected data was then analyzed using multiple linear regression techniques to explore the relationship and impact between the independent variables—service quality and product availability—and the dependent variable, customer reviews. The findings reveal that both product availability and service quality positively and significantly affect customer reviews. Interestingly, service quality has a stronger influence compared to product availability. These results suggest that enhancing service quality, alongside ensuring adequate product availability, is crucial for increasing positive customer reviews on TokoteknoPro. The insights from this study can help TokoteknoPro's management develop more effective strategies to enhance customer experience and optimize customer reviews.